Achieving the Company's Competitive Advantage by Improving Service Quality - Irma Setyawati (Global Writing Academica Researching & Publishing, 2022)
The capacity of a business to get new clients and keep the ones they already have is directly correlated to its chances of surviving in the market. Compared to its rivals, a firm has a competitive advantage if it is in a stronger position to attract and retain consumers and defend itself against other businesses' aggressive activities. Therefore, the quality of the service will then become a strategic component that will offer an edge over the competition. The purpose of this essay is to investigate the connection between providing high-quality service and gaining a competitive advantage for major businesses operating in the market. This investigation combines a qualitative strategy with a descriptive research methodology. According to the findings of the study, providing superior customer service is the most effective method for businesses to differentiate themselves from their competitors and build up their competitive advantages. As a result, businesses need to transform themselves into learning and knowledge-creating organizations that enable the implementation of continuous improvement plans with incredible speed and efficiency, constantly striving to gain benefits and thus have a superior orientation to clients.